2018
DOI: 10.1108/f-08-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Performance indicators for facilities operation and maintenance (Part 2)

Abstract: Purpose This paper (Part 2 of 2) aims to shortlist performance indicators which are used in evaluating facilities operation and maintenance (O&M) in commercial buildings. Design/methodology/approach A three-session focus group meeting, with the use of a customized questionnaire and audio recording, was convened to solicit opinions from O&M experts. Their quantitative responses (ratings on the importance of the indicators) and the qualitative ones (reasons for having the indicators selected or exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Different types of KPIs were discussed in this study. In [8], authors developed the performance indicators to operate and maintain an enterprise. The presence of a wide variety of analytics tools assists enterprises to organize their departments and employees in a better way.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Different types of KPIs were discussed in this study. In [8], authors developed the performance indicators to operate and maintain an enterprise. The presence of a wide variety of analytics tools assists enterprises to organize their departments and employees in a better way.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, a demand for KPI which reveals hidden pattern via intelligent and hierarchical analysis of organizational tree structure. KPIs are essential to effective management by identifying underperforming aspects of the business as well as that demand increased resources [8]. It will report events that may signify problems that arise internally within the organization's operations or potential threats resulting from external events may provide management with rich information to improve the organization's strategies [6].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Intended to develop a performance evaluation scheme for commercial buildings, a literature review identified over 70 applicable performance indicators (Lai and Man, 2018a). A focus group meeting was then convened, resulting in a shortlist of indicators categorized into five groups: physical, financial, task and equipment related, environmental, and health, safety and legal (Lai and Man, 2018b). A questionnaire survey was made to single out the most important indicators (i.e.…”
Section: Literature Review: Groundwork Of the Research Teammentioning
confidence: 99%